Asynchronous Programming with C++. - Javier Reguera-Salgado; Juan Antonio Rufes; PACKT (GB: Packt, 2024)
Design and develop high-performance software solutions by using concurrent and asynchronous techniques provided by the most modern features in C++20 and C++23 Key Features Learn how to use modern C++ features, including futures, promises, async, and coroutines to build asynchronous solutions Develop cross-platform network and low-level I/O projects with Boost.Asio Master optimization techniques by understanding how software adapts to machine hardware Purchase of the print or Kindle book includes a free PDF eBook Book Description As hardware advancements continue to accelerate, bringing greater memory capacity and more CPU cores, software must evolve to adapt to efficiently use all available resources and reduce idle CPU cycles. In this book, two seasoned software engineers with about five decades of combined experience will teach you how to implement concurrent and asynchronous solutions in C++. You'll gain a comprehensive understanding of parallel programming paradigms-covering concurrent, asynchronous, parallel, multithreading, reactive, and event-driven programming, as well as dataflows-and see how threads, processes, and services are related. Moving into the heart of concurrency, the authors will guide you in creating and managing threads and exploring C++'s thread-safety mechanisms, including mutual exclusion, atomic operations, semaphores, condition variables, latches, and barriers. With this solid foundation, you'll focus on pure asynchronous programming, discovering futures, promises, the async function, and coroutines. The book takes you step by step through using Boost.Asio and Boost.Cobalt to develop network and low-level I/O solutions, proven performance and optimization techniques, and testing and debugging asynchronous software. By the end of this C++ book, you'll be able to implement high-performance software using modern asynchronous C++ techniques. What you will learn Explore the different parallel paradigms and know when to apply them Acquire deep knowledge of thread management and safety mechanisms Understand asynchronous programming in C++, including coroutines Leverage network asynchronous programming by using Boost.Asio and Boost.Cobalt Add proven performance and optimization techniques to your toolbox Find out how to test and debug asynchronous software Who this book is for This book is for developers who have some experience using C++, regardless of their professional field. If you want to improve your C++ skills and learn how to develop high-performance software using the latest modern C++ features, this book is for you.
Data in extended ASCII character set.
Mode of access: Internet.